Business information systems (BIS) adoption in agri-food sector and the 'transaction climate' determinant. (1st January 2014) - Zioupou, Sophia; Andreopoulou, Zacharoula; Manos, Basil; Kiomourtzi, Fedra
Presently, firms aiming to improve competitiveness and business practices introduce innovative BIS models and e-business organisational schemas. This paper is based on the theoretical model proposed by Patterson et al. (2003) quoting seven BIS adoption determinants. It is attempted to update, adapt and apply this model in agri-food sector, for the case of Greece, regarding the 5th determinant in the BIS adoption model, referred as 'transaction climate' between partners, representing relationships between business organisations. Twenty variables were initially proposed to decide on the 'transaction climate' determinant related to customers, suppliers, carriers and 3rd party logistics providers. Through factor analysis, it was provided a two-factor model, to be used as a validated determinant that can be applied in wider context. Business managers' suggestion on this model can identify the current existing climate for organisational and technological change between the firm's partners and decide to proceed in BIS adoption and development.